ANALISIS DAMPAK KEPRIBADIAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI - Salju Salju (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
Employee performance is an important element that influences the success and efficiency of the organization as a whole. Personality and good communication are very important to support employee performance. A good personality and strong communication skills can be trained and developed through proper training, experience and support. It is important for organizations to encourage and support personality development and positive communication to improve employee performance. This study aims to determine the impact of personality and communication on employee performance. Determining the number of samples used in this study is done using the census method, where the total population of 37 employees is also used as a sample. The data analysis method used is multiple linear regression analysis. The research findings prove that personality and communication have a significant positive impact on employee performance.